Commentary to the book PAPALINI, Vanina, editor 2019 The memory between politics andethics. Collected texts of Héctor Schmuder (1979-2015) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Let me start with a personal memory. In February 2007 I met a young woman of origin Chilean and Swedish nationalized who, with a subsidy from the government of this second country, through Chiapas, Mexico to do a volunteer service. One day, like any other, it was brimming with happiness: his mothers name appeared on the list of victims of State Terror of the period of the dictatorship. It was the culmination of a long struggle of a family that, from different latitudes of the world, were subsumed in the social history and historical memory of a period when the only option in force for the regime was the annihilation of the political adversary. The questions are too many, but perhaps of greater importance to know yes in the exercise of memory Is there, in fact, some point arrival?The answer seems negative, since in recent years Historical Memory has experienced a certain resurgence political and academic. I certainly agree with Schmucler that politically «A brilliant multiplication of the use of the word memory stamped in public actions [] it is a simulacrum (pp. 431). In academics I ponder that importance in the recent publication, besides the selection and edition of Papalini to the works of Héctor «Toto» Schmucler, of five books more on that axis from different latitudes of Latin America from Soriano (2019), Casaús (2019), Lara (2018), La Casa de Todos y Todos (2018) and Arfuch (2018).
Keywords: Politics; ethics; memory; hector Schmucler